Extract Corn Silk with Variation of Solvents on Yield, Total Phenolics, Total Flavonoids and Antioxidant Activity - Haslina Haslina; Murtiari Eva (Indonesian Food and Nutrition Progress, 2017)
Corn silk is a by product or waste that is commonly used as a traditional medicine that contain bioactive compounds such as volatile oils, steroids, alkaloids, tannins, flavonoids, chlorogenic acid and phenolic compounds, containing protein, carbohydrates, minerals (Ca, Mg, Cu , Zn, Fe and Mn), higher crude fiber, vitamin B, vitamin C, vitamin K, steroids such as sitosterol and stigmasterol, alkaloids, saponins, tannins, flavonoids, anthocyanins, protokatekin, vanilic acid, derivatives hasperidin and quersetin, phenols, terpenoids and glycosides, maysin, β-carotene, beta-sitosterol, geraniol, hordenin, limonene, menthol and viteskin also a good source of poliphenol as antioksidan. Solvent used for the extraction of flavonoid compounds are methanol, ethanol, acetone and ethyl acetate. Basic separation by solvent extraction is the difference in the solubility of each composition in compaction with solvent. Solubility is influenced temperature, stirring speed, the extraction time, comprehensive tangent plane solids by solvent extraction and frequency.This study aims to extract corn silk by using a variation of solvent type in terms of yield, total phenols, flavonoids and antioxidant activity.The experimental design used in this study is completely randomized design (CRD) 1 factor with 5 replications. Solvent: methanol: water (85:15) (v/v) ethanol: water (85:15) (v/ v), ethyl acetate: water (85:15) (v/v), acetone: water (85 : 15) (v/v). Furthermore, the data obtained were analyzed variants and if there is a difference between treatments continued by Duncan Multiple Range Test (DMRT) at 5% level.Variations in the type of solvent significant (p <0.05) to the yield, total phenol, total flavonoids and antioxidant activity. Variations in the type of solvent with the highest yield at a ratio (methanol: water), and the ratio (ethanol: water), then the ratio (acetone: water) and the lowest ratio of (ethyl acetate: water). At ratio (methanol: water) obtained yield is 65.8%, total phenol ie 45350.27 mg / kg GAE, total flavonoids 291.28 mg QE / kg and activities of antioxidant that is 92.1%.